Agroecological tourism: a transdisciplinary approach for sustainable development in rural areas - Fernández , Alfonso José (SATHIRI, 2025)
This article describes the transdisciplinary approach of agroecological tourism as a strategy for sustainable development in rural areas in the state of Barinas. Agroecological tourism has established itself as a promising alternative for sustainable development in rural areas, offering a series of economic, social and environmental benefits to local communities. However, to achieve truly sustainable development, it is essential to adopt a transdisciplinary approach that integrates various perspectives and disciplines. In this sense, the methodology used in this study was based on in-depth interviews with specialists trained in the Diploma in Agroecological Tourist Routes for Sustainable Development. Through descriptive research with a qualitative approach, three stages were implemented, using epistemic matrices for data collection. The results obtained in this study suggest that agroecological tourism is a viable and sustainable alternative for rural development in various regions of the world. Based on the conclusions and recommendations derived from this approach, it can be stated that the transdisciplinary approach to agroecological tourism provides significant advantages for sustainable development in rural areas. It is crucial to understand this tourism modality as a complex system that interacts with its environment, promoting the active participation of local communities in decision-making and in the design of agroecological tourism strategies.
Keywords: Agroecological; Transdisciplinary Tourism; Sustainable Development; Rural Areas; Strategies